Isomorphism in nominative models of abstract substantives with state of mind and physical state meaning - Заманова, Ілона Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
In the article, the author studies the isomorphism of nominative models of the fields of spiritual state and physical state, noting that the isomorphism is manifested at all language levels. The presence of significant number lexemes with the erased inner form that binds the nomination of person spiritual condition field with the subjects physical condition field, as well as the presence of semantically stable constructions like the ardor of character, one of which members is also a sign of a physical object, shows that the phenomenon of this isomorphism was inherent in the language over a long period of historical development. Syntactic derivatives with the meaning of a spiritual state are formed from verbs that nominate physical states and processes. Isomorphism of spiritual and physical nominative models is connected with the phenomenon of language economy. According to observations, language, if possible, tends to minimize forms despite to the wealth of meanings; when it comes about spiritual state nomination, the speaker chooses the form which describes the material visible world, what is tangible to all people. The premise of that was such a feature of human perception as synesthesia. The isomorphism of nominating the spiritual and physical state greatly contributed to the objectification and personification of abstract concepts, which affects the consciousness of speakers as well as the conceptualization of ‘state of mind’ nature. The article also notes that the active process in modern language is the expansion of the abstract substances semantics and an increase in the number of concepts with a much more extended abstraction, due to this, the field of a person’s spiritual state can also be replenished. Abstraction and extended abstraction are distinguished by the author. Extended abstraction is formed on the basis of polysemicity, the main feature of the extended abstract concept is the expansion of the semantic structure and the formation of a new semantic core, different from the generating base. The article provides examples of semantic abstraction expanding in the abstract substances.